Hyperuricemia: Features of the Diet - O. B. Shvabskaia; O. V. Izmailova; N. S. Karamnova; O. M. Drapkina (Столичная издательская компания, 2022)
The association of hyperuricemia (HU) with cardiovascular disease (CVD), diabetes, metabolic syndrome, and kidney disease has been demonstrated in numerous studies. НU is the main pathogenetic factor in the development of gout and is associated with an increase in overall and cardiovascular mortality. НU is included in the list of factors determining cardiovascular risk. According to epidemiological studies, there is a high prevalence of HU in the world and its increase in recent decades. A number of factors have been identified that contribute to the increased risk of НU. Non-modifiable factors include gender, age, genetic factors, and modifiable factors include diet and lifestyle. Nutritional unbalances, increased life expectancy, increased prevalence of obesity, and increased use of drugs (especially diuretics) are seen as contributing factors to the rise in НU. The review was carried out to summarize the available information on the effect of dietary habits, individual foods and nutrients on serum uric acid (SUA) levels and the risk of developing HU. The review presents the results of scientific studies demonstrating the relationship of НU with the consumption of foods rich in purines (offal, red meat, fish, seafood, legumes), alcohol consumption, drinks sweetened with fructose, coffee, dairy products, vegetables and fruits. Diet correction is an important and necessary step in the prevention and treatment of НU. The article reviews the basic principles of dietary management in HU and provides dietary recommendations for patients. For effective prevention and treatment of НU, a mandatory correction of the diet is required.